Influence of various pilot hole profiles on pedicle screw fixation strength in minimally invasive and traditional spinal surgery: a comparative biomechanical study - Li, Yun-Da; Lai, Po-Liang; Hsieh, Ming-Kai; Chen, Weng-Pin; Lee, De-Mei; Tsai, Tsung-Ting; Tai, Ching-Lung (Frontiers in Bioengineering and Biotechnology, 2024)
Despite advancements in pedicle screw design and surgical techniques, the standard steps for inserting pedicle screws still need to follow a set of fixed procedures. The first step, known as establishing a pilot hole, also referred to as a pre-drilled hole, is crucial for ensuring screw insertion accuracy. In different surgical approaches, such as minimally invasive or traditional surgery, the method of creating pilot holes varies, resulting in different pilot hole profiles, including variations in size and shape. The aim of this study is to evaluate the biomechanical properties of different pilot hole profiles corresponding to various surgical approaches.Commercially available synthetic L4 vertebrae with a density of 0.16 g/cc were utilized as substitutes for human bone. Four different pilot hole profiles were created using a 3.0 mm cylindrical bone biopsy needle, 3.6 mm cylindrical drill, 3.2-5.0 mm conical drill, and 3.2-5.0 mm conical curette for simulating various minimally invasive and traditional spinal surgeries.Two frequently employed screw shapes, namely cylindrical and conical, were selected.Following specimen preparation, screw pullout tests were performed using a material test machine, and statistical analysis was applied to compare the mean maximal pullout strength of each configuration.Conical and cylindrical screws in these four pilot hole configurations showed similar trends, with the mean maximal pullout strength ranking from high to low as follows: 3.0 mm cylindrical biopsy needle, 3.6 mm cylindrical drill bit, 3.2-5.0 mm conical curette, and 3.2-5.0 mm conical drill bit. Conical screws generally exhibited a greater mean maximal pullout strength than cylindrical screws in three of the four different pilot hole configurations. In the groups with conical pilot holes, created with a 3.2-5.0 mm drill bit and 3.2-5.0 mm curette, both conical screws exhibited a greater mean maximal pullout strength than did cylindrical screws.